Study on the Effect of Salinity and Water Content on CBM Adsorption/Desorption Characteristics of Coal Reservoir in Baode Block. (21st May 2022) - Zhang, Wei; He, Yanxiang; Zhang, Qingfeng; Meng, Yanjun; Liu, Tuo; Meng, Wenhui; Zuo, Yun; Fan, Hongbo
Abstract : The adsorption/desorption characteristics of a coal reservoir play an important role in coalbed methane (CBM) development. The proximate analysis, maceral analysis and methane isothermal adsorption/desorption experiment are carried out based on coal samples from no. 4+5 coal seam in Baode block. Combing with coal experimental data and the CBM well-produced water salinity data in the Baode block, the effect of salinity and water content on CBM adsorption/desorption characteristics of the coal reservoir and its influencing mechanism is discussed. The results show that the CBM adsorption and desorption capacity decreases with the increase of water salinity and the decrease value shows a decreasing trend. The increase of water salinity reduces the solubility of methane in coal seam water and then reduces the adsorption capacity of methane. With the increase of water content, the adsorption and desorption capacities of CBM decrease gradually. The CBM adsorption and desorption capacities decrease with the increase of water content in coal samples. The adsorption/desorption capacities of coal samples change rapidly in the low-water content stage and slowly in the high-water content stage. The competitive adsorption effect and water blocking effect between water and methane molecules are the main influencing mechanisms of water content on CBM adsorption/desorption. It can be seen that the salinity and water content will have a certain adverse impact on the adsorption and desorption capacity of CBM in the Baode block. The influence of the difference in water content and salinity in the coal seam cannot be ignored in reserve evaluation and productivity prediction of CBM. The continuous, stable, and effective drainage is one of the key factors to ensure the efficient development of CBM wells in the Baode block.